Penerapan Media Pembelajaran Berbasis Assemblr Edu Pada Mata Pelajaran IPS untuk Meningkatkan Hasil Belajar Siswa SMP Negeri 1 Gunungsitoli - Jernih Waty Batee; Eka Septianti Laoli; Wahyutra Adilman Telaumbanua; Bezisokhi Laoli (Universitas Negeri Medan, 2025)
The purpose of this study was to determine the application of Assemblr Edu-based learning media in social studies subjects in improving the learning outcomes of students of SMP Negeri 1 Gunungsitoli in the 2024/2025 academic year. This research is a class action research (PTK). This research was conducted at SMP Negeri 1 Gunungsitoli, in the even semester of the 2024/2025 academic year, the subjects in this study were VII grade students totaling 32 people. The research instruments used were (1) teacher observation sheets, (2) student observation sheets, (3) photos/documentation, (4) learning outcome tests. Based on the researcher's findings that: (1) the average result of the teacher observation sheet in cycle I was 62.49% and in cycle II teacher observation increased to 90.83%. (2) while the average student activity observation sheet results in cycle I were 60.7% and in cycle II increased with an average of 84.45%. Based on the evaluation results, the average student learning outcomes in cycle I were 67.86% with a completeness percentage level of 46.87%. While in cycle II it increased with an average learning outcome of 83.5% with a percentage level of completeness of 90.62%. Based on these results, this study has reached the predetermined target of 75%. Thus, the researchers concluded that there was an increase in student learning outcomes in grade VII social studies subjects through the application of Assemblr Edu-based media to improve student learning outcomes at SMP Negeri 1 Gunungsitoli.